Removal of Copper(II) Ions from Aqueous Solutions. I. Adsorption Studies Using Powdered Marble Wastes as Sorbent - S.E. Ghazy; S.E. Samra; A.M. Mahdy; S.M. El-Morsy (Adsorption Science & Technology)
Batch adsorption experiments of copper(II) ions from aqueous solutions on to powdered marble wastes (PMW) have been performed. The latter is an effective inorganic sorbent which is inexpensive, widespread and may represent an environmental problem. The main parameters influencing the sorption process, i.e. initial solution pH, sorbent and Cu 2+ ion concentrations, stirring times and temperature, were examined. The results obtained revealed that the sorption of Cu 2+ ions on to PMW was endothermic in nature and followed first-order kinetics. Moreover, it was well described by the Langmuir, Freundlich and Dubinin–Radushkevich (D–R) adsorption models over the concentration range studied. Under the optimum experimental conditions employed, the removal of ca. 100% Cu 2+ ions was attained.